Root cause failure analysis - Mobley, R. Keith, 1943- (Boston : Newnes, 1999)
Root Cause Failure Analysis provides the concepts for performing industrial troubleshooting investigations. It describes the methodology to perform Root Cause Failure Analysis (RCFA), a topic in maintenance engineering. It also includes equipment design and troubleshooting guidelines, which are used to perform RCFA on machinery found in most production facilities.
General analysis techniques -- Root cause failure analysis methodology -- Safety-related issues -- Regulatory compliance issues -- Process performance -- Pumps -- Fans, blowers, and fluidizers -- Conveyors -- Compressors -- Mixers and agitators -- Dust collectors -- Process rolls -- Gearboxes/reducers -- Steam traps -- Inverters -- Control valves -- Seals and packing -- Pumps -- Fans, blowers, and fluidizers -- Conveyors -- Compressors -- Mixers and agitators -- Dust collectors -- Process rolls -- Gearboxes or reducers -- Steam traps -- Inverters -- Control valves -- Seals and packing -- Others.
Includes bibliographical references and index.
Keywords: Plant maintenance; System failures (Engineering); Machines; Onderhoud; Electronic books